CARBON CONTENT OF PHYTOPLANKTON AND BACTERIA IN AN ESTUARINE SYSTEM - Ma'ruf Kasim (JOURNAL OF COASTAL DEVELOPMENT, 2011)
Carbon content of diatom, dinoflagellates and bacteria were studied in order to estimate the living particulate organic carbon (LPOC) in an estuarine system. In the water column, diatoms were most abundant in spring than the other seasons. Dinoflagellates, cyanobacteria, and microzooplankton were present in all seasons, even low in cell numbers. The highest abundance of bacteria was at inner region of estuary and lowest at the mouth of Bekanbeusi River. The percentage of benthic diatom to total diatoms assemblages on sediment surface was higher than that in the water column. The POC in water column was composed of 13 – 24 % for diatoms and 0.6 – 1.6 % for dinoflagelate in carbon base throughout a year. The contribution of diatom carbon to total POC showed highest percentage in June (24 %) in the Akkeshi-ko estuary. In general, bacterial carbon was lower than that of diatoms carbon. On average, the contribution of bacterial carbon was 5-8 % to the total POC throughout a year.